Long-Term Soy Protein Isolate Consumption Reduces Liver Steatosis Through Changes in Global Transcriptomics in Obese Zucker Rats - Kozaczek, Melisa; Bottje, Walter; Kong, Byungwhi; Dridi, Sami; Albataineh, Diyana; Lassiter, Kentu; Hakkak, Reza (Frontiers in Nutrition, 2020)
To understand how soy protein isolate (SPI) reduced liver steatosis in male obese Zucker rats, we conducted global gene expression (RNAseq) analysis on liver samples of male rats fed either the SPI or a control casein (CAS)-based diet (n=8 per group) for 16 wks. Liver transcriptomics was analyzed using an Ilumina HiSeq system with 2X100 base pair paired-end reads method. Bioinformatics was conducted using Ingenuity Pathway Analysis (IPA) software (Qiagen, CA) with P < 0.05 and 1.3 fold differential expression cutoff values. Regression analysis between RNAseq data and targeted mRNA expression analysis of 12 top differentially expressed genes (from the IPA program) using quantitative PCR (qPCR) revealed a significant regression analysis (r2=0.69, P= 0.0008). In addition, all qPCR values had qualitatively similar direction of up- or down-regulation compared to the RNAseq transcriptomic data. An assessment of diseases and functions based on differentially expressed target molecules in the dataset revealed that lipid metabolism was predicted to be enhanced whereas inflammatory response was predicted to be inhibited in SPI-fed compared to CAS-fed rats at 16 weeks. Using the upstream regulator analysis and regulator effects functions of the IPA program enables the prediction of upstream regulators (e.g. transcription regulators) that could be playing important roles in attenuating or promoting liver steatosis due to SPI or CAS diets. Examples of upstream regulators that were predicted to be activated (based on expression of down-stream target molecules) that were linked to increased conversion of lipid and transport of lipid in SPI-fed rats included hepatocyte nuclear factor 4 alpha (HNF4A) and aryl hydrocarbon receptor (AHR). Examples of upstream regulators that were predicated to be activated in CAS-fed rats that were linked to predicted activation of phagocytosis and neutrophil chemotaxis included colony stimulating factor 2 and tumor necrosis factor. The results provide clear indication that long-term SPI-fed rats exhibited diminished inflammatory response and increased lipid transport in liver compared to CAS-fed rats that likely would contribute to reduced liver steatosis in this obese Zucker rat model.